Composite sandwich repair using through-thickness reinforcement with robotic hand micro-drilling. (15th September 2020) - Suresh, M.; Sanders, A.; Prajapati, P.; Kaipa, K.; Kravchenko, O.G.
Abstract: The novel through-thickness reinforcement and repair (TTR) method of composite sandwich structures with delamination or disbond damage is proposed. The technique allows to restore the load-carrying capacity of composite sandwich structures with delamination and disbond damage and after complete facesheet laminate failure. The developed TTR repair technique was investigated using 4-point bending configuration. The conducted digital image correlation analysis showed that TTR allowed to suppress buckling in disjointed laminate. The TTR method offers the potential way for reinforcing and repair of composite sandwich structures, providing improvement of maximum load-carrying capacity. The high level of reconfigurability of the present TTR technique was achieved by incorporating the robotic hand micro-drilling setup, which uses a force-controlled drilling process with safe human-robot collaboration features. The effectiveness of the method was shown to strongly depend on the aspect ratio of the embedded TTR carbon fiber pin.